Pengaruh Kualitas Audit dan Karakteristik Perusahaan terhadap Income Smoothing pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Sri Hardyanti; Nurul Hayat; Dian Urna Fasihat (AKUNTANSI 45, 2026)
This study aims to analyze the effect of audit quality and company characteristics on the practice of income smoothing in manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The independent variables in this study consist of audit quality, company size, profitability, leverage, and company age, while the dependent variable is income smoothing measured using the Eckel Index. This study employs a quantitative approach with a causal associative research method. The data used are secondary data in the form of annual financial statements obtained from the official website of the Indonesia Stock Exchange. The sampling technique used was purposive sampling, resulting in 84 companies with a total of 252 observation data. Data analysis was conducted using multiple linear regression through descriptive statistical tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination. The results show that audit quality, company size, profitability, leverage, and company age do not have a significant effect on the practice of income smoothing, either simultaneously or partially. The F-test significance value of 0.457 indicates that all independent variables collectively are unable to explain variations in income smoothing. In addition, the low coefficient of determination indicates that income smoothing practices are influenced by other factors outside the research model. The classical assumption tests demonstrate that the regression model fulfills the assumptions of normality and is free from multicollinearity, heteroscedasticity, and autocorrelation problems.